Analisis Potensi Limbah Penebangan dan Pemanfaatannya pada Hutan Jati Rakyat di Kabupaten Bone - . Mujetahid M. A. Mujetahid M. (Biocelebes, 2010)
The study was aimed to analyze cutting waste potency and prospect of its utilization. The study results showed that waste volume per tree was 0.01-0.14 m3 at average of 0.07 (17.11%) comprising of main trunk waste of 0.03 m3 (39.84%), stump waste of 0.01 m3 (12.11%), crotches-free upper waste of 0.03 m3 (28.49%) and crotches of 0.02 m3 (19.56%) with potency amounting of 19,498.17 m3 of all ready-to-feeling trees of 266,005 trees and utilized as basic materials for furniture and charcoal industries. Key words: Waste, cutting, community teak forest.